A epistemologia e a psicologia de Jean Piaget e as neurociências uma revisão sistemática - Obana, João Enzio Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aims to investigate, in the scientific literature, what are and how are the scientific studies being developed that seek to relate Epistemology and Genetic Psychology of Jean Piaget with Neurosciences, and what are the possible contributions of neurosciences to Education. Methods and procedures: This study was conducted under systematic review. The procedure included the location, selection and analysis of studies indexed in the databases: Scopus, BIREME, Sage Journals, IEEE, PubMed, Oxford Press Journals and ERIC, taking as search keywords: Piaget and Neuroscience. Results: 145 articles were found, which were analyzed based on predefined categories that allowed the organization of a database in order to facilitate the crossing of identified information. 76 studies remained after the first exclusions. With the analysis of the abstracts of the remaining studies, 28 studies were obtained. These 28 studies were read in full, and those not related directly to the themes were excluded, leaving 17 studies for Systematic Review. Conclusion: After due analysis, it was concluded the studies have direct or indirect relations between the theories (Piagetian and Neuroscience). Direct in bringing principles Piagetian principles combined with neuro-scientific experiments. The Piagetian hypotheses related to cognitive development are in many ways confirmed by Neuroscience. However, there is no direct relationship with Education or any educational profile issues.

Este estudo objetiva investigar, na literatura científica, quais são e como estão sendo desenvolvidos os estudos científicos que buscam relacionar a Epistemologia e Psicologia Genéticas de Jean Piaget com as Neurociências e, quais possíveis contribuições desses estudos para a Educação. Métodos e procedimentos: Esta pesquisa foi realizada mediante revisão sistematizada. Teve como procedimento a localização, seleção e análise de estudos indexados em bases de dados: Scopus, BIREME, Sage Journals, IEEE, PubMed, Oxford Press Journals e ERIC, tendo-se como descritores de busca: Piaget and Neuroscience. Resultados: Foram localizados 145 artigos, os quais foram analisados com base em categorias pré-definidas, que permitiram a organização de um banco de dados, de forma a propiciar o cruzamento das informações identificadas. Após as primeiras exclusões restaram 76 estudos. Com a análise dos abstracts dos estudos restantes, obteve-se 28 estudos. Estes 28 foram lidos na íntegra e excluiu-se os que não relacionavam diretamente o temas, restando 17 estudos incluídos para a Revisão Sistemática. Conclusão: Após a análise devida, concluiu-se que os estudos apresentam relações diretas ou indiretas entre a teorias (piagetianas e da Neurociências). Diretas no sentido de trazer princípios piagetianos aliados à experimentação neurocientífica. As hipóteses piagetianas sobre o desenvolvimento cognitivo são em muitos aspectos confirmadas pelas Neurociências. Contudo, não há relações diretas com a Educação ou quaiquer questões de cunho pedagógico.
Keywords: Epistemologia genetica; Psicologia genetica; Neurociências; Educação; Neurosciences